Two steps forward, one step back: What research progressions have been made to support the advancement of health and performance in pregnant international and world-class sportswomen since 2016? A scoping review - Kirsty J. Elliott-Sale; Jodie G. Dakic; Marlize De Vivo; Grainne M. Donnelly; Deirdre McGhee; Jane Thornton; Kathleen Stroia; Christopher Kronk; Melanie Hayman (Women's Health)
Background: With more elite sportswomen incorporating pregnancy into their athletic careers, it is imperative that they are supported with evidence informed guidelines for healthy, safe pregnancies. Objectives: To (i) provide a rapid review, which mapped fields of study relevant to what is known about the health and performance-related considerations for pregnant elite sportswomen, and (ii) quantify the overall state of the art since the 2016/2017 International Olympic Committee publications on exercise and pregnancy in recreational and elite athletes. Eligibility Criteria: Original, empirical, peer-reviewed, English-language studies reporting on research conducted with or related to healthy, pregnant elite (international and world-class) sportswomen aged ⩾18 and ⩽40 years were eligible for this review. In addition, all aspects and/or metrics of health and sports performance were considered, and both quantitative and qualitative research designs were included. Sources of Evidence: PubMed, SPORTDiscus and Web of Science were systematically searched. Reviews, book chapters and grey literature were excluded. Reference lists of eligible studies were also searched to identify additional studies of relevance. Charting Methods: Scoping review with expert consultation exercise. Consideration was given to basic numerical analysis of the extent, distribution, and nature of the studies included in the review. Five key stakeholders, including physiotherapists, physicians, applied practitioners and researchers, with expertise in women’s and pelvic health, pregnancy and postpartum, breast biomechanics and rehabilitation and training in national and international-level sport took part in an expert consultation process. Results: Eight studies were identified as part of the literature review, and more than 30 topics were highlighted through consultation as areas of interest and further study related to the health and performance of elite pregnant sportswomen. Conclusion: In the last decade, an insufficient number of studies have been conducted, related to pregnant international and world-class sportswomen, meaning that the state of the art on this topic for this specific population has not changed to a noticeable degree. Experts in this area still have a plethora of unanswered research questions, such that it is still impossible to take a fully research informed approach to supporting pregnant elite sportswomen.